Անգլերեն և հայերեն հանպատրաստից խոսքի ընդհատումների մի քանի պատճառների մասին - Աբրահամյան, Կ․ Շ․; Վելյան, Կ․ Ա.
В статье рассматривается одна из неотьемлемых черт спонтанной речи, а именно синтаксические прерывания или, иначе - синтаксические “аварии”. Последние имеют целый ряд как формальных признаков, так и причин. Предметом анализа в данной статье являются основные свойства одного из подтипов мини-аварий -разнородные по своим функциональным характеристикам речевые исправления. Как показывают данные анализа, речевые исправления свойственны как английской, так и армянской спонтанной речи, что позволяет предположить их универсальный характер. The article discusses one of the inherent features of spontaneous talk, namely, syntactic interruptions,or syntactic “accidents”, put otherwise. The latter have a wide range of formal properties, as well as reasons behind them. The article highlights the key properties of one subtype of mini-accidents, more specifically – speech repairs, which are not functionally homogenous. As the data for analysis indicate, speech repairs can be found both in English and Armenian, which suggests that speech repairs and syntactic interruptions caused by them could be considered to be a universal phenomenon.
Keywords: Լեզվաբանություն